Awareness and attitude of the public toward personalized medicine in Korea - Lee, Iyn Hyang; Kang, Hye Young; Suh, Hae Sun; Lee, Sukhyang; Oh, Eun Sil; Jeong, Hotcherl (PLoS ONE, 2018)
Objectives As personalized medicine (PM) is expected to greatly improve health outcomes, efforts have recently been made for its clinical implementation in Korea. We aimed to evaluate public awareness and attitude regarding PM. Methods We performed a self-administered questionnaire survey to 703 adults, who participated in the survey on a voluntary basis. The primary outcome measures included public knowledge, attitude, and acceptance of PM. We conducted multinomial multivariate logistic analysis for outcome variables with three response categories and performed multivariate logistic regression analyses for dichotomous outcome variables. Results Only 28% of participants had knowledge that genetic factors can contribute to inter-individual variations in drug response and the definition of PM (199 out of 702). Higher family income was correlated with greater knowledge concerning PM (OR = 3.76, p = 0.034). A majority of respondents preferred integrated pharmacogenomic testing over drug-specific testing and agreed to inclusion of pharmacogenomic testing in the national health examination (64% and 77%, respectively), but only 51% were willing to pay for it. Discussion Our results identify the urgent need for public education as well as the potential health disparities in access to PM. This study helps to frame policies for implementing PM in clinical practice.
Keywords: Adult; Attitude to Health; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Middle Aged; Patient Education as Topic; Pharmacogenomic Testing; Precision Medicine; Public Health; Republic of Korea; Surveys and Questionnaires; Young Adult